IMPROVING THE QUALITY OF FUN LEARNING THROUGH A PROJECT BASED LEARNING MODEL FOR EARLY CHILDHOOD TEACHERS IN TAMBUN UTARA BEKASI REGENCY - Eva Susana; Lilis Suryani; Siti Zaitun; Retno Zen Astuti; Nyai Mumun; Repita Jahra; Rohayati; Ade Ahmad Ghozali (International Conferences on Early Childhood Education Proceedings, 2024)
Early childhood has different early characteristics and abilities, so learning is needed that can optimize various aspects of development according to their abilities and characteristics. So teachers are needed who are able to create a fun and child-centered learning atmosphere. There are still many early childhood teachers in the North Tambun area, Bekasi Regency who use conventional learning. So far, teaching and learning activities are still teacher-centered, pursuing material completion targets, and leaving aside fun and child-centered learning. One of the efforts to provide knowledge and insight and improve the skills of early childhood teachers in the North Tambun area of Bekasi Regency in creating a pleasant learning atmosphere, researchers conducted research in the area by holding workshops and mentoring activities. This activity is also expected to motivate early childhood teachers to be able to apply the knowledge gained into daily learning activities.  This workshop will be held on October 21-28, 2023 at TK Penguin Family Islamic School 02 Tambun Utara, Bekasi Regency, West Java Province. Then continued with mentoring at 10 institutions on October 22-27, 2023. The method that researchers use is Classroom Action research which is carried out in one cycle. The results obtained, teachers are able to apply the Project Based Learning Model  in learning activities. This is based on the increase in the average pre-test results  compared to post-test. This situation can be used as a benchmark that there has been an increase in the competence capacity of early childhood educators who become trainees from before and after attending the training. These results can be input for various stakeholders,